Expert Evaluation of Artificial Intelligence Chatbots for Central Auditory Processing Disorder Information - Davidson, Alyssa J.; Jedrzejczak, W Wiktor; McCullagh, Jennifer; Ferre, Jeanane M.; Bradbury, Amy; Palmer, Shannon B.; Iliadou, Vasiliki M.; Musiek, Frank E. (American journal of audiology, 2026)
PURPOSE: Artificial intelligence (AI) chatbots based on large language models (LLMs) can deliver medical information, but their performance on specialized topics such as central auditory processing disorder (CAPD) remains unexplored. This study evaluated the accuracy and completeness of three AI chatbots (ChatGPT, Gemini, and Claude) in providing CAPD-related information across varying levels of question complexity. METHOD: Forty-four questions, categorized into four difficulty levels (patient level, easy, intermediate, and specialized; n = 11 each), were submitted to each chatbot, generating 132 responses. Seven clinical experts, blinded to chatbot identity, independently rated accuracy and completeness on a 1-5 Likert scale. Data were analyzed with analyses of variance, correlations, and interrater comparisons. RESULTS: Chatbot performance was similar, with mean accuracy below 4.0 and completeness about 3.5. Complex questions often scored below 3.0 across experts. Only three of the 44 questions, primarily patient level or relatively simple, received consistently high expert ratings (≥ 4 for both accuracy and completeness) across all three chatbots. Performance declined with question difficulty, although differences were not statistically significant. Accuracy and completeness were correlated across chatbots. CONCLUSIONS: Current AI chatbots provided generally accurate CAPD information but fell short of clinical standards, particularly on specialized questions. Their limited performance underscores the need for clinician oversight in CAPD assessment and management. Chatbots may serve as helpful adjuncts but should not replace expert evaluation and guidance in clinical settings. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.31975101.
Keywords: dept.cmd

Expert evaluation of artificial intelligence chatbots for central auditory processing disorder information - Davidson, Alyssa; Jedrzejczak, W.; McCullagh, Jennifer; Ferre, Jeanane; Bradbury, Amy; Palmer, Shannon; Iliadou, Vasiliki; Musiek, Frank (American Journal of Audiology, 2026)
Keywords: Chatbot; Completeness (order theory); Expert system; Inter-rater reliability; Psychometrics; Telemedicine; dept.cmd

Incorporating gender-inclusive language in undergraduate courses on anatomy and physiology of the speech mechanism - Smith, Julian; Smith, Keith; White, Evan (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: Competence (human resources); Cultural competence; Curriculum; English language; Language acquisition; Mechanism (biology); Multiculturalism; dept.cmd

Identifying the association between post-extubation laryngeal edema and aspiration in acute respiratory failure patients - DM, Lucas; R, Peterson; J, Rieck; M, Owusu; E, McNally; R, Scheel; P, Cavanagh; S, Langmore; A, Kearney; J, Levitt; J, Siner; R, Vojnik; et al. (European Archives of Oto-Rhino-Laryngology, 2026)
Keywords: Acute pulmonary edema; Acute respiratory failure; Aspiration; Deglutition disorders; Edema; Laryngeal Edema; Laryngeal edema; Larynx; Post-extubation dysphagia; Pulmonary edema; Respiratory failure; dept.cmd

Reliability of Lingual Swallow Pressure Measurements in Healthy Older and Younger Adults - Smith, Julian; Murray, Kelsey; Szynkiewicz, Sarah; Wasiuk, Peter; Dalton, M; Thompson, Kirsty; Kamarunas, Erin (Journal of Oral Rehabilitation, 2025)
Keywords: Bolus (digestion); Mastication; Measurement device; Reliability (semiconductor); Swallowing; dept.cmd; dysphagia; lingual strength; reliability; swallow pressureswallowingtongue strength

Imaging of the Velopharynx: Nasopharyngoscopy - Kummer, Ann W.; Mabry, Kelly (Cleft Palate and Velopharyngeal Dysfunction: A Multidisciplinary Approach to Evaluation and Management, 2025)
Nasopharyngoscopy is a minimally invasive endoscopic procedure that allows visual observation and analysis of the velopharyngeal mechanism during speech. It can be used to assess both anatomic and physiologic abnormalities of the velopharyngeal valve. In cases of suspected velopharyngeal insufficiency (VPI), nasopharyngoscopy is particularly useful in determining the size, location, and cause of the velopharyngeal opening. This information is very important for surgical planning. Nasopharyngoscopy is also useful in the assessment of secondary surgery that was done for VPI. It can help determine the need for revision and the type of revision surgery that is most likely to be successful. The purpose of the chapter is to explain how nasopharyngoscopy is used in the evaluation of velopharyngeal function. This chapter includes specific tips for achieving a successful examination in children as young as age 3. Finally, important observations from nasopharyngoscopy are described. © 2025 The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Hypernasality; Instrumental assessment; Medicine; Nasal emission; Nasendoscopy; Nasopharyngoscopy; Resonance disorder; Velopharyngeal dysfunction; Velopharyngeal incompetence; Velopharyngeal insufficiency; Velopharyngeal valve; dept.cmd

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

Oral Reading Assessment: Four Conditions Where Caution Is Warranted - Zipoli, R.P.; Ramachandar, S. (Assessment for Effective Intervention, 2023)
Assessments of oral reading are widely used for screening, progress monitoring, and comprehensive evaluations. Despite the utility and technical adequacy of these tools, there are subgroups of students for whom measures of oral reading may be inappropriate. The first section of this article focuses on how tests of oral reading may underestimate word reading ability and reading fluency among four subgroups of students with speech, language, or learning difficulties. These include school-age students who demonstrate word-finding difficulties (which are common among students with a learning disability or developmental language disorder), developmental stuttering, childhood apraxia of speech, and pediatric dysarthria. The second section offers practical recommendations for more accurate assessment procedures, correct placement decisions, relevant professional learning activities, and strategic interdisciplinary teaming. © Hammill Institute on Disabilities 2023.
Keywords: communication disorders; dept.cmd; learning disability; peer-reviewed; reading/literacy

Predicting speech-in-speech recognition: Short-term audibility and spatial separation - Wasiuk, P.A.; Calandruccio, L.; Oleson, J.J.; Buss, E. (Journal of the Acoustical Society of America, 2023)
Quantifying the factors that predict variability in speech-in-speech recognition represents a fundamental challenge in auditory science. Stimulus factors associated with energetic and informational masking (IM) modulate variability in speech-in-speech recognition, but energetic effects can be difficult to estimate in spectro-temporally dynamic speech maskers. The current experiment characterized the effects of short-term audibility and differences in target and masker location (or perceived location) on the horizontal plane for sentence recognition in two-talker speech. Thirty young adults with normal hearing (NH) participated. Speech reception thresholds and keyword recognition at a fixed signal-to-noise ratio (SNR) were measured in each spatial condition. Short-term audibility for each keyword was quantified using a glimpsing model. Results revealed that speech-in-speech recognition depended on the proportion of audible glimpses available in the target + masker keyword stimulus in each spatial condition, even across stimuli presented at a fixed global SNR. Short-term audibility requirements were greater for colocated than spatially separated speech-in-speech recognition, and keyword recognition improved more rapidly as a function of increases in target audibility with spatial separation. Results indicate that spatial cues enhance glimpsing efficiency in competing speech for young adults with NH and provide a quantitative framework for estimating IM for speech-in-speech recognition in different spatial configurations. © 2023 Acoustical Society of America.
0 citations (Crossref) [2023-10-31]
Keywords: dept.cmd; peer-reviewed

Aphasia, alexia, and agraphia - Purdy, Mary H. (Encyclopedia of Mental Health, Third Edition: Volume 1-3, 2023)
Aphasia is a language disorder that occurs as a result of brain damage. It affects auditory comprehension, verbal expression, reading, and writing due to the disruption of specific language components such as phonology, semantics, and/or syntax. A hallmark characteristic of aphasia is anomia, or impaired word retrieval. This may occur in the context of fluent speech (normal rate, rhythm and prosody) or nonfluent speech (hesitant and agrammatic verbal output). Other characteristics of aphasia vary depending on the specific location and extent of brain damage. Alexia and agraphia are acquired impairments in reading and writing, respectively. These deficits may occur in isolation but more commonly co-occur with aphasia. Assessment and treatment of aphasia, alexia, and agraphia focuses on identifying and restoring impaired function as well as determining the impact of the impairment of quality of life and developing compensatory strategies to manage persisting deficits. This article describes the symptoms associated with aphasia, alexia, and agraphia, the subtypes and neurological correlates of each impairment, the general trajectory of recovery, and assessment and treatment approaches. © 2023 Elsevier Inc. All rights reserved.
Num Pages: V1-131
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; dept.cmd

Utilization of instrumentation in swallowing assessment of surgical patients during COVID-19 - Warner, Heather; Coutinho, Jennifer M.; Young, Nwanmegha (Life, 2023)
The aim of this study is to describe a measured return to instrumental dysphagia assessments for our vulnerable surgical patient population, such that best practice patterns could be resumed and our staff kept safe from transmission of COVID-19. A retrospective medical record review provided data on clinical practice patterns of swallowing assessment in an at-risk surgical patient population. Outcomes of this study support protocols that allow clinicians to safely resume the use of instrumental assessment and return to best practice in dysphagia assessment for our surgical patient population.
0 citations (Crossref) [2023-10-31] Number: 7
Keywords: COVID-19; Fiberoptic Endoscopic evaluation of swallowing; deglutition; dept.cmd; dysphagia; peer-reviewed; surgical; swallowing assessment

A cross-sectional investigation of disfluencies in typically developing Spanish-English bilingual children - Rojas, Raúl; Irani, Farzan; Gusewski, Svenja; Camacho, Natalia (Journal of Fluency Disorders, 2023)
Purpose This study examined the language skills and the type and frequency of disfluencies in the spoken narrative production of typically developing Spanish-English bilingual children. Method A cross-sectional sample of 106 bilingual children (50 boys; 56 girls) enrolled in kindergarten through Grade 4, produced a total of 212 narrative retell language samples in English and Spanish. A specialized fluency coding system was implemented to index the percentage of total (%TD) and stuttering-like disfluencies (%SLD) in each language. Large-scale reference databases were used to classify children’s dual language proficiency profiles (balanced, English dominant, Spanish dominant) based on language sample analysis measures of morphosyntax and lexical diversity. Results The bilingual Spanish-English children in this study did not demonstrate significant cross-linguistic differences for mean %TD or %SLD. However, the mean %TD and %SLD in both languages exceeded the risk threshold based on monolingual English-speaking norms. English dominant bilingual children demonstrated significantly lower %TD in English than Spanish. Spanish dominant children demonstrated significantly lower %SLD in Spanish than English. Conclusions This study included the largest sample size of bilingual Spanish-English children investigated to date from a fluency perspective. The frequency of disfluencies was found to be variable across participants and change dynamically as a function of grade and dual language proficiency profiles, indicating the need for studies that employ larger sample sizes and longitudinal designs.
0 citations (Crossref) [2023-10-31]
Keywords: Bilingual children; Disfluencies; Language sample analysis; Narratives; Stuttering; dept.cmd; peer-reviewed

The influence of side-lying position on oropharyngeal swallow function in at-risk infants: an exploratory study - Smith, Julian B.; Kamarunas, Erin; O’Donoghue, Cynthia (Clinical Pediatrics, 2023)
This investigation assessed the effect of side-lying position on infant oropharyngeal swallow physiology. Infant modified barium swallow studies (MBS) recordings were retrospectively examined in matched-pairs comparing at-risk infants swallowing in both an upright/cradled position and a side-lying position. Swallow parameters were measured independently and through a consensus coding approach. Infants fed in side-lying position showed a decrease in airway invasion severity as compared with when those same infants were fed in an upright/cradled position (P = .009). Bolus location at the time of swallow initiation was higher when infants were fed in side-lying position as compared with cradle position (P = .024), representing decreased risk of airway invasion. Infants fed in side-lying position demonstrated fewer swallows per breaths (P = .032). This pilot study validates the need for additional research to further define the mechanisms related to this improvement, and to determine how diagnosis and medical stability moderate these findings.
0 citations (Crossref) [2023-10-31]
Keywords: dept.cmd; peer-reviewed

Interdisciplinary considerations for diagnosing aphasia in the schizoaffective patient: A case report - Warner, Heather; Cometz, Alexa (International Journal of Language & Communication Disorders, 2023)
Background Patients with schizophrenia present with both cognitive impairment as well as language difficulties. There are similarities in the language output of patients with schizophrenia and patients with aphasia, thus a differential diagnosis of patients who present with a question of dual diagnoses can be a clinical challenge. This case report highlights the importance of an interdisciplinary approach to a patient with schizophrenia who benefitted from intervention from both psychiatry and speech–language pathology services due to the patient's unique verbal output. Aims The primary aim of this case report is to highlight the critical importance of interdisciplinary collaboration in this patient population. The secondary aim is to disseminate an interesting and unique clinical phenomenon whereby the patient demonstrated an awareness of two distinct speech patterns and the unique ability to ‘code switch’ between them, something not commonly appreciated in this clinical population. Methods & Procedures This case report describes a patient seen as part of routine clinical care. Information shared was solely observational and involved dissemination of information regarding case history, assessment and treatment plan. No interventions were implemented as a part of this study. Outcomes & Results Interprofessional communication was critical in order to diagnose a patient with schizophrenia with an atypical speech pattern. The patient's language output did not manifest as a true aphasia but rather as two distinct language patterns that the patient could use at will. This ability to ‘code switch’ between languages is a unique clinical profile that is atypical of patients with schizophrenia. WHAT THIS PAPER ADDS What is already known on this subject Contemporary literature discusses the similarities between the language patterns of patients with aphasia and those with schizophrenia. There has been debate about how to classify and identify the mechanism of schizophrenic language. It is unclear whether the tangential press of speech in schizophrenia is a consequence of a formal thought disorder, or whether it constitutes an actual disorder or expressive language. Additionally, the mechanism for this speech pattern is not well defined in the literature as there is no consensus on whether it is a breakdown in linguistic processing or simply a patient's disordered thoughts being put into words. A less robust literature exists that suggests that there is a cognitive mechanism responsible for these speech patterns, as tangential speech has been linked to poor goal maintenance in other types of cognitive tasks. What this paper adds to existing knowledge This study adds an important discussion about the critical importance of interprofessional collaboration when differentially diagnosing this complex patient population. It highlights the importance of the clinical exchange of information between the two disciplines of psychiatry and speech–language pathology about a patient population where clinical information is intertwined in the way described above. Regardless of the cause of the disordered output, what is lacking in the literature is evidence of how to address the complexities of the output of these patients and how to best manage the care of the patient. This study adds a practical clinical approach to collaborating on the assessment and management of this complex patient population. Importantly, it adds a description of a clinical manifestation of the language output of a patient with schizophrenia that we do not believe to have been previously published in the literature. What are the potential or actual clinical implications of this work? Implications of this study include a much-needed shift in the field in two regards. First, to include this patient population in the groups of patients that can benefit from interprofessional collaboration for differential diagnosis and consideration for speech and language therapy. Second, it offers a practical clinical approach to inter-professional management in this patient population, something the literature is currently lacking. Additionally, publication of this unique clinical manifestation provides foundational knowledge for other clinicians appreciating similar clinical patterns of language output. To our knowledge, this is the first published case in which a patient could volitionally inhibit certain speech characteristics and thus this case study may assist in future differential diagnosis of patients with schizophrenia.
1 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1460-6984.12801
Keywords: aphasia; dept.cmd; interprofessional practice; language disorders; peer-reviewed; schizoaffective disorder

Effects of Teacher-Delivered eCoaching on Paraeducators and Students with Autism Spectrum Disorder - Horn, A.L.; Rock, M.L.; Douglas, K.H.; Bean, K.M.; Layden, S.J.; Roitsch, J. (Education and Training in Autism and Developmental Disabilities, 2022)
Paraeducators often support students with the most intensive academic, life, and behavioral needs, which includes students with intellectual and other developmental disabilities (IDD; e.g., autism spectrum disorder; ASD), yet they typically enter the classroom with inadequate preparation to perform their roles effectively. Using a multiple-baseline research design replicated across participants, we evaluated the effects of job-embedded bug-in-ear (BIE) coaching delivered by the teacher on paraeducators’ use of behavior specific praise (BSP) while teaching transition-age students with ASD. Findings confirmed each of the three paraeducators immediately increased the percentage of occurrence and rate per minute in which they offered BSP. They sustained these high levels during fading. Further, the special education teacher, who served as the eCoach, and the paraeducators reported BIE was an effective form of paraeducator professional development. Finally, changes in expressive social and communicative behaviors were observed in student participants as a result of the intervention. These results extend literature on BSP and also help establish BIE coaching as an evidence-based practice for paraeducators. © Division on Autism and Developmental Disabilities.
Keywords: dept.cmd; peer-reviewed; ⛔ No DOI found

Making Sense of Word Reading Difficulties: Principles of Clinical Assessment - Zipoli, Richard P. (Communication Disorders Quarterly, 2022)
Speech-language pathologists (SLPs) are increasingly called upon to help assess students with word-recognition difficulties, including dyslexia. Although SLPs tend to have comparatively strong knowledge regarding the phonological awareness skills that support word reading, findings from survey research indicate that many SLPs report limited knowledge and training on word recognition and phonics. The purpose of this article is to provide a systematic framework for assessing and interpreting students’ word reading skills. Five potential components of word reading assessment will be examined: word recognition, phonological decoding, automaticity, performance with specific phonics patterns, and reading multimorphemic and multisyllabic words. Emphasis will be given to how specific test formats and procedures can be used to help identify patterns of word reading difficulty.
0 citations (Crossref) [2023-10-31]
Keywords: assessment; automaticity; decoding; dept.cmd; peer-reviewed; phonics; reading; word recognition

Best Practice in Swallowing Assessment in COVID-19 - Warner, Heather; Young, Nwanmegha (Dysphagia, 2022)
The COVID-19 pandemic has significantly altered the world as we know it. Service delivery for the instrumental evaluation of dysphagia in hospitalized patients has been significantly impacted. In many institutions, instrumental assessment was halted or eliminated from the clinical workflow, leaving clinicians without evidence-based gold standards to definitively evaluate swallowing function. The aim of this study was to describe the outcomes of an early, but measured return to the use of instrumental dysphagia assessment in hospitalized patients during the COVID-19 pandemic. Data was extracted via a retrospective medical record review on all patients on whom a swallowing consult was placed. Information on patient demographics, type of swallowing evaluation, and patient COVID status was recorded and analyzed. Statistics on staff COVID status were also obtained. Over the study period, a total of 4482 FEES evaluations and 758 MBS evaluations were completed. During this time, no staff members tested COVID-positive due to workplace exposure. Results strongly support the fact that a measured return to instrumental assessment of swallowing is an appropriate and reasonable clinical shift during the COVID-19 pandemic.
1 citations (Crossref) [2023-10-31]
Keywords: COVID; Deglutition; Dysphagia; FEES; Swallowing assessment; dept.cmd; peer-reviewed

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
4 citations (Crossref) [2023-10-31]
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Teaching Children with Autism to Create Multi-symbol Messages on Augmentative Alternative Communication Applications During Play - Gevarter, Cindy; Najar, Adriana Medina; Siciliano, Mariah (Advances in Neurodevelopmental Disorders, 2022)
Research involving the use of augmentative and alternative communication (AAC) applications on mobile technology devices for children with autism spectrum disorder (ASD) needs to expand beyond teaching simple requesting skills. Children’s abilities to create multi-symbol AAC messages is one skill that can be further explored.
3 citations (Crossref) [2023-10-31]
Keywords: Augmentative alternative communication; Autism; Multi-symbol messages; Naturalistic intervention; dept.cmd; peer-reviewed

A parent-implemented embedded AAC intervention for teaching navigational requests and other communicative functions to children with Autism spectrum disorder. - Gevarter, Cindy; Groll, Mariah; Stone, Erin; Najar, Adriana Medina (Augmentative and alternative communication (Baltimore, Md. : 1985), 2021)
This study evaluated the effectiveness of an embedded naturalistic intervention for teaching augmentative and alternative communication (AAC) application responses to three preschool-aged males with autism spectrum disorder (ASD). Parents were taught to embed opportunities for their child to communicate with a grid-based AAC application during every-day routines such as play or mealtime. Communication targets included requesting objects using two-step taxonomic navigational responses, and requesting assistance, rejecting items, or making social comments/responses using a two-step message-strip response. During intervention, parents used strategies such as time delay, prompting, reinforcement, and device proximity (faded over time) to encourage target responses. Display formats and intervention targets were selected in consideration of prior dynamic assessment results. Effects of intervention were evaluated using a multiple probe across participants design. For functional navigational AAC item requesting, all three participants showed an immediate increase in responding that maintained at high levels. Functional AAC responding for other communicative purposes also increased, but at a more gradual pace. All three participants showed generalized responding when new items were added to displays, and when display pages with a larger array of folders and vocabulary items were introduced. Generalization to labeling tasks was mixed. © 2021 International Society for Augmentative and Alternative Communication.
4 citations (Crossref) [2023-10-31]
Keywords: Alternative communication; Augmentative and alternative communication application; Augmentative-and-alternative communication; Autism spectrum disorders; Communication application; Communicative functions; Diseases; Embedded instruction; Human rehabilitation engineering; Naturalistic intervention; Navigation; Steps responding; Two-step responding; dept.cmd; peer-reviewed

Naturalistic communication training for early intervention providers and latinx parents of children with signs of autism. - Gevarter, Cindy; Najar, Adriana Medina; Flake, Jennifer; Tapia-Alvidrez, Felicia; Lucero, Alixandria (Journal of developmental and physical disabilities, 2021)
In this study, researchers implemented a brief training plus coaching program in naturalistic developmental behavioral intervention with three participant triads. Each triad consisted of an early intervention provider, an English-speaking Latinx parent, and that parent’s young child with autism spectrum disorder (ASD) or early signs of ASD who had limited vocal speech. The effects a single training session, plus two researcher coaching sessions were evaluated using a nonconcurrent multiple probes across participants design. Primary dependent variables included (a) the number of completed targeted communication turns between the parent and child and (b) the number of child independent target communication responses (gestures and manual signs) during family-selected routines. Additional measures examined whether parents used strategies taught to them during training, and whether early intervention providers addressed strategies taught via coaching. A social validity measure was used to determine parent and provider views of the training. Due to COVID-19 restrictions, training and post-training sessions were delivered via telehealth for two triads. While data trends and variability differed across triads, following training, all three families increased the number of completed target communication turns and all three children showed higher rates of independent communication responses. Parents and providers implemented strategies taught and reported positive effects of the program. Implications regarding the use of naturalistic intervention methods for Latinx families, the utility of brief training models to meet the needs of under-resourced early intervention programs, and potential uses of telehealth are discussed. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
9 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8079838 ; https://europepmc.org/article/MED/33935477 ; https://link.springer.com/content/pdf/10.1007/s10882-021-09794-w.pdf ; https://www.scilit.net/article/c889ef228cfa367aafde22446e957a7d?action=show-references ; https://pubmed.ncbi.nlm.nih.gov/33935477/
Keywords: dept.cmd; peer-reviewed

Correction to: Abnormalities of aspiration and swallowing function in survivors of acute respiratory failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather L.; White, S. David; Dvorkin, Daniel; Fink, Daniel S.; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2021)
Due to the errors occurred in the originally published version, this article is being reprinted in its entirety as Correction. All errors have been corrected. It is the correct version. © 2021, Springer Science+Business Media, LLC, part of Springer Nature.
1 citations (Crossref) [2023-10-31]
Keywords: dept.cmd; erratum; peer-reviewed

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101017685
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

The Association Between Endotracheal Tube Size and Aspiration (During Flexible Endoscopic Evaluation of Swallowing) in Acute Respiratory Failure Survivors - Krisciunas, Gintas P.; Langmore, Susan E.; Gomez-Taborda, Stephanie; Fink, Daniel; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Scheel, Rebecca; Rubio, Alix C.; Siner, Jonathan M.; Vojnik, Rosemary; Warner, Heather; et al. (Critical Care Medicine, 2020)
Objectives: To determine whether a modifiable risk factor, endotracheal tube size, is associated with the diagnosis of postextubation aspiration in survivors of acute respiratory failure. Design: Prospective cohort study. Setting: ICUs at four academic tertiary care medical centers. Patients: Two hundred ten patients who were at least 18 years old, admitted to an ICU, and mechanically ventilated with an endotracheal tube for longer than 48 hours were enrolled. Interventions: Within 72 hours of extubation, all patients received a flexible endoscopic evaluation of swallowing examination that entailed administration of ice, thin liquid, thick liquid, puree, and cracker boluses. Patient demographics, treatment variables, and hospital outcomes were abstracted from the patient's medical records. Endotracheal tube size was independently selected by the patient's treating physicians. Measurements and Main Results: For each flexible endoscopic evaluation of swallowing examination, laryngeal pathology was evaluated, and for each bolus, a Penetration Aspiration Scale score was assigned. Aspiration (Penetration Aspiration Scale score ≥ 6) was further categorized into nonsilent aspiration (Penetration Aspiration Scale score = 6 or 7) and silent aspiration (Penetration Aspiration Scale score = 8). One third of patients (n = 68) aspirated (Penetration Aspiration Scale score ≥ 6) on at least one bolus, 13.6% (n = 29) exhibited silent aspiration, and 23.8% (n = 50) exhibited nonsilent aspiration. In a multivariable analysis, endotracheal tube size (≤ 7.5 vs ≥ 8.0) was significantly associated with patients exhibiting any aspiration (Penetration Aspiration Scale score ≥ 6) (p = 0.016; odds ratio = 2.17; 95% CI 1.14-4.13) and with risk of developing laryngeal granulation tissue (p = 0.02). Conclusions: Larger endotracheal tube size was associated with increased risk of aspiration and laryngeal granulation tissue. Using smaller endotracheal tubes may reduce the risk of postextubation aspiration. © 2020 International Anesthesia Research Society.
15 citations (Crossref) [2023-10-31] WOS:000576935300034
Keywords: Adult; Aged; Airway extubation; Deglutition; Deglutition disorders; Female; Humans; Intensive Care Units; Intratracheal intubation; Intubation; Intratracheal; Male; Middle Aged; Prospective Studies; Respiration; Artificial; Respiratory Aspiration; Respiratory Insufficiency; Respiratory aspiration; Respiratory distress syndrome; Risk Factors; Survivors; acid aspiration; adverse event; aged; artificial ventilation; clinical trial; dept.cmd; devices; endotracheal intubation; female; human; intensive care unit; male; middle aged; multicenter study; peer-reviewed; physiology; procedures; prospective study; respiratory failure; risk factor; survivor; swallowing

Development of an Accurate Bedside Swallowing Evaluation Decision Tree Algorithm for Detecting Aspiration in Acute Respiratory Failure Survivors - Moss, Marc; White, S. David; Warner, Heather; Dvorkin, Daniel; Fink, Daniel; Gomez-Taborda, Stephanie; Higgins, Carrie; Krisciunas, Gintas P.; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; et al. (Chest, 2020)
Background: The bedside swallowing evaluation (BSE) is an assessment of swallowing function and airway safety during swallowing. After extubation, the BSE often is used to identify the risk of aspiration in acute respiratory failure (ARF) survivors. Research Question: We conducted a multicenter prospective study of ARF survivors to determine the accuracy of the BSE and to develop a decision tree algorithm to identify aspiration risk. Study Design and Methods: Patients extubated after ≥ 48 hours of mechanical ventilation were eligible. Study procedures included the BSE followed by a gold standard evaluation, the flexible endoscopic evaluation of swallowing (FEES). Results: Overall, 213 patients were included in the final analysis. Median time from extubation to BSE was 25 hours (interquartile range, 21-45 hours). The FEES was completed 1 hour after the BSE (interquartile range, 0.5-2 hours). A total of 33% (70/213; 95% CI, 26.6%-39.2%) of patients aspirated on at least one FEES bolus consistency test. Thin liquids were the most commonly aspirated consistency: 27% (54/197; 95% CI, 21%-34%). The BSE detected any aspiration with an accuracy of 52% (95% CI, 45%-58%), a sensitivity of 83% (95% CI, 74%-92%), and negative predictive value (NPV) of 81% (95% CI, 72%-91%). Using recursive partitioning analyses, a five-variable BSE-based decision tree algorithm was developed that improved the detection of aspiration with an accuracy of 81% (95% CI, 75%-87%), sensitivity of 95% (95% CI, 90%-98%), and NPV of 97% (95% CI, 95%-99%). Interpretation: The BSE demonstrates variable accuracy to identify patients at high risk for aspiration. Our decision tree algorithm may enhance the BSE and may be used to identify patients at high risk for aspiration, yet requires further validation. Trial Registry: ClinicalTrials.gov; No.: NCT02363686; URL: www.clinicaltrials.gov; © 2020 American College of Chest Physicians
13 citations (Crossref) [2023-10-31] WOS:000596845800029
Keywords: Airway Extubation; Algorithms; Article; Decision Trees; Deglutition; Female; Humans; Male; Point-of-Care Testing; Predictive Value of Tests; Reproducibility of Results; Respiration; Artificial; Respiratory Aspiration; Respiratory Insufficiency; Risk Assessment; Survivors; Symptom Assessment; United States; acid aspiration; acute respiratory failure; adult; adverse event; aged; algorithm; artificial ventilation; aspiration; bedside swallowing evaluation; clinical trial; controlled study; decision tree; dept.cmd; diagnostic accuracy; diagnostic test accuracy study; digestive system examination; dysphagia; epidemiology; extubation; female; flexible endoscopic evaluation of swallowing; gastrointestinal endoscopy; high risk patient; human; intubation; major clinical study; male; multicenter study; oxygen; oxygen therapy; pathophysiology; peer-reviewed; point of care testing; predictive value; priority journal; procedures; prospective study; pulmonary aspiration; reproducibility; respiratory failure; risk assessment; sensitivity and specificity; speech language pathologist; survivor; swallowing; symptom assessment

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
12 citations (Crossref) [2023-10-31] WOS:000516272800002
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education; Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students; Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Abnormalities of Aspiration and Swallowing Function in Survivors of Acute Respiratory Failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather; White, S. David; Dvorkin, Daniel; Fink, Daniel; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2020)
The mechanisms responsible for aspiration are relatively unknown in patients recovering from acute respiratory failure (ARF) who required mechanical ventilation. Though many conditions may contribute to swallowing dysfunction, alterations in laryngeal structure and swallowing function likely play a role in the development of aspiration. At four university-based tertiary medical centers, we conducted a prospective cohort study of ARF patients who required intensive care and mechanical ventilation for at least 48 h. Within 72 h after extubation, a Fiberoptic Flexible Endoscopic Evaluation of Swallowing (FEES) examination was performed. Univariate and multivariable analyses examined the relationship between laryngeal structure and swallowing function abnormalities. Aspiration was the primary outcome, defined as a Penetration- Aspiration Scale (PAS) score of 6 or greater. Two other salient signs of dysphagia—spillage and residue—were secondary outcomes. A total of 213 patients were included in the final analysis. Aspiration was detected in 70 patients (33%) on at least one bolus. The most commonly aspirated consistency was thin liquids (27%). In univariate analyses, several abnormalities in laryngeal anatomy and structural movement were significantly associated with aspiration, spillage, and residue. In a multivariable analysis, the only variables that remained significant with aspiration were pharyngeal weakness (Odds ratio = 2.57, 95%CI = 1.16–5.84, p = 0.019) and upper airway edema (Odds ratio = 3.24, 95%CI = 1.44–7.66, p = 0.004). These results demonstrated that dysphagia in ARF survivors is multifactorial and characterized by both anatomic and physiologic abnormalities. These findings may have important implications for the development of novel interventions to treat dysphagia in ARF survivors. Clinical Trials Registration ClinicalTrials.gov Identifier: NCT02363686, Aspiration in Acute Respiratory FailureSurvivors. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
10 citations (Crossref) [2023-10-31] WOS:000587104600002
Keywords: Deglutition; Deglutition Disorders; Humans; Prospective Studies; Respiratory Aspiration; Respiratory Insufficiency; Survivors; acid aspiration; dept.cmd; dysphagia; human; peer-reviewed; prospective study; respiratory failure; survivor; swallowing

Babysitter training guide for families with individuals with ASD - Bean, K; Neers, K; Cook, Barbara; Eren, R (Encyclopedia of Autism Spectrum Disorders, 2020)
The Second Edition of this major reference work expands its coverage and continues to break new ground as an electronic resource for students, educators, researchers, and professionals. Comprehensive in breath and textbook in depth, the Second Edition of the Encyclopedia of Autism Spectrum Disorders serves as a reference repository of knowledge in the field as well as a regularly updated conduit of new knowledge long before such information trickles down from research to standard textbooks. The Second Edition of the Encyclopedia digests and presents new and updated information for readers who need to stay current with the latest research and clinical practices, including advances in neurobiology and genetics, diagnostic instruments and assessment tests, pharmaceutical treatments, and behavioral, speech and language, and other rehabilitative therapies. The Second Edition of the Encyclopedia covers topics across the following major conceptual areas of ASD and PDDs, including: Research trends and findings Behavior/speech Communication TreatmentsEducation Taking advantage of the techniques offered by the electronic medium, the Second Edition of the Encyclopedia of Autism Spectrum Disorders offers an extensive cross-referencing system facilitating search and retrieval of information. This unique, comprehensive Second Edition of the Encyclopedia of Autism Spectrum Disorders is an essential reference for advanced undergraduate and graduate students as well as researchers, professors, clinicians, and other practitioners across such related disciplines as developmental psychology, child and adolescent psychiatry, social work, child and school psychology, behavioral therapy, and sociology of education.
Keywords: dept.cmd